Formation and breakdown of death domain oligomers - Boo, Zhao Zhi (Nanyang Technological University, 2020)
Innate immune signaling involves formation of large signaling complexes through death domain homotypic interactions, allowing rapid signal amplification to facilitate inflammatory signaling. The formation and breakdown of these immune complexes allow modulation of innate immune responses. Elucidating the structures of death domain filaments is an important step in understanding the signaling mechanisms of these pathways. Conversely, the hijacking of innate immune proteins by pathogens to carry out immune evasion is also well studied. However, there is little known information on direct degradation of death domain complexes by pathogens. In this thesis, the formation and breakdown of two innate immune adaptor filaments were studied. Firstly, the structure of the CARD domain filament of apoptosis- associated speck-like protein containing a CARD (ASC) was investigated. This was achieved by reconstituting ASC CARD filament in vitro by refolding bacteria expressed recombinant ASC CARD monomers. Cryoelectron microscopy was used to image the filaments to obtain micrographs and images were processed using RELION. Helical reconstruction yielded a 4.1 Å resolution structure of ASC CARD filament. Secondly, the bacterial modulation of death domain signaling was investigated. This was done by screening reconstituted myeloid differentiation primary response gene 88 (Myd88) DD filaments against bacterial secretions in vitro. Characterization of bacterial secretions indicated that pseudolysin secreted by Pseudomonas aeruginosa modulates mammalian inflammatory response through degradation of Myd88 DD. The findings of this thesis can contribute to the existing knowledge of both the formation and breakdown of innate immune signalosomes.